Study protocol for the implementation and evaluation of the Self-harm Assessment and Management for General Hospitals programme in Ireland (SAMAGH) - Ella Arensman; M. Isabela Troya; Sarah Nicholson; Anvar Sadath; Grace Cully; Ana Paula Ramos Costa; Ruth Benson; Paul Corcoran; Eve Griffin; Eileen Williamson; Joe Eustace; Frances Shiely; et al. (BMC, 2020)
Abstract Background Previous self-harm is one of the strongest predictors of future self-harm and suicide. Increased risk of repeated self-harm and suicide exists amongst patients presenting to hospital with high-risk self-harm and major self-harm repeaters. However, so far evidence-based training in the management of self-harm for mental health professionals is limited. Within this context, we aim to develop, implement and evaluate a training programme, SAMAGH, Self-harm Assessment and Management Programme for General Hospitals in Ireland. SAMAGH aims to (a) reduce hospital-based self-harm repetition rates and (b) increase rates of mental health assessments being conducted with self-harm patients. We also aim to evaluate the training on self-harm knowledge, attitudes, and skills related outcomes of healthcare professionals involved in the training. Methods/design The study will be conducted in three phases. First, the SAMAGH Training Programme has been developed, which comprises two parts: 1) E-learning Programme and 2) Simulation Training. Second, SAMAGH will be delivered to healthcare professionals from general hospitals in Ireland. Third, an outcome and process evaluation will be conducted using a pre-post design. The outcome evaluation will be conducted using aggregated data from the National Self-Harm Registry Ireland (NSHRI) on self-harm repetition rates from all 27 public hospitals in Ireland. Aggregated data based on the 3-year average (2016, 2017, 2018) self-harm repetition rates prior to the implementation of the SAMAGH will be used as baseline data, and NSHRI data from 6 and 12 months after the implementation of SAMAGH will be used as follow-up. For the process evaluation, questionnaires and focus groups will be administered and conducted with healthcare professionals who completed the training. Discussion This study will contribute to the evidence base regarding the effectiveness of an evidence informed training programme that aims to reduce repeated hospital self-harm presentations and to improve compliance with self-harm assessment and management. This study is also expected to contribute to self-harm and suicide training with the possibility of being translated to other settings. Its feasibility will be evaluated through a process evaluation.